Patients with crush syndrome and kidney disease: lessons learned from the earthquake in Kahramanmaras,, Türkiye - Ozturk, Savas; Tuglular, Serhan; Olmaz, Refik; Kocyigit, Ismail; Kibar, Muge Uzerk; Turgutalp, Kenan; Sever, Mehmet Sukru (Elsevier Science Inc, 2024)
This study investigated in-hospital outcomes and related factors in patients diagnosed with postearthquake crush syndrome after the earthquakes in Kahramanmaras,, T & uuml;rkiye. One thousand twenty-four adult patients diagnosed with crush syndrome were analyzed. and outcomes were collected. A total of 9.8% of patients died during their hospital stay. Nonsurvivors were generally older, more likely to have preexisting chronic kidney disease, and faced more severe injuries and complications, including hypotension-shock, arrhythmias, elevated markers of renal dysfunction, and higher rates of acute kidney injury (AKI) and compartment syndrome. In addition, intensive care unit needs were higher. Multivariate analysis confirmed that age, injury severity, shock, high potassium, uric acid, and lactate levels on admission, development of AKI, compartment syndrome, and intensive care unit admission were significant predictors of mortality. Better disaster preparedness and improved health care infrastructure could be potential explanations for improved in-hospital mortality in the current era, as compared to previous earthquakes.
Keywords: crush; earthquake; mortality; renal disaster; Turkiye